Plant growth-promoting microorganisms as natural stimulators of nitrogen uptake in citrus - Ana Pérez-Piqueres; Belén Martínez-Alcántara; Rodolfo Canet; Raquel del Val; Ana Quiñones (PLoS ONE, 2025)
Improving nitrogen uptake efficiency by citrus in Mediterranean areas, where this crop predominates, is crucial for reducing ground-water pollution and enhancing environmental sustainability. This aligns with the Farm to Fork Strategy (European Green Deal) objectives, which aim to reduce the use of mineral fertilizers by up to 20% and to eliminate soil contamination from nitrogen entirely. In this context, exploring the potential of plant growth-promoting bacteria application to reduce nutrient inputs is a promising opportunity. The objective of the present study was to evaluate the effect of two Bacillus subtilis strains either individually inoculated or in combination with Saccharomyces cerevisiae on 15N-labeled fertilizer uptake efficiency and physiological parameters. Individual inoculations positively affected tree water potential, leaf chlorophyll concentrations (SPAD-values) and photosynthetic performance, enhancing tree growth. Fertilizer-15N use efficiency increased, as did phosphorus and potassium uptakes. Conversely, no response was observed in the trees co-inoculated with S cerevisiae. Therefore, PGPB can be considered an interesting means to reduce reliance on synthetic fertilizers in citrus orchards, minimizing the environmental impact and promoting sustainable production practices.